The Impact of Using Dialogue Journals in Teaching Writing skills to Level 1 (EFL Major Students) at Faculty of Languages and Translations, King Khalid University - Mohamed, Karem AbdelAtif Ahmed; Siddiqui, Ahlullah (International Journal of Psychosocial Rehabilitation, 2020)
Good writing skill is important for English as Foreign Language (EFL) major students as they need to write a lot especially when they reach advance stage of their undergraduate program. It has been perceived EFL major students at KKU, usually transfer the stylistic features of their first language, Arabic to the target language, English, for instance they often talk around the topic and repeat phrases before stating the main points. This study aims to investigate the impact of using Dialogue Journals in teaching writing skills to level 1, EFL major students at Faculty of Languages and Translation, King Khalid University, Saudi Arabia. The study had a pre-post control group design. Two groups of students was randomly assigned to the control and experimental group. Students of the experimental group was instructed using Dialogue Journals writing (DJW), whereas the control group received no such instruction and received the usual treatment (teacher’s written comments). Each student was required to write 24 journal entries at two journal entries per week. Tools of study included a rubric (a composition grading scale). Evaluative exam was conducted to measure the progress made. Instruction was carried out by the researchers for both groups. (T) Test was used to analyze obtained data. Pedagogical implications for (EFL) writing instruction are provided.